The Allosteric Hemoglobin Effector ITPP Inhibits Metastatic Colon Cancer in Mice. Issue 5 (November 2017) - Limani, Perparim; Linecker, Michael; Schneider, Marcel A.; Kron, Philipp; Tschuor, Christoph; Kachaylo, Ekaterina; Ungethuem, Udo; Nicolau, Claude; Lehn, Jean-Marie; Graf, Rolf; Humar, Bostjan; Clavien, Pierre-Alain
Abstract : Objective: To test the effects of enhanced intracellular oxygen contents on the metastatic potential of colon cancer. Background: Colorectal cancer is the commonest gastrointestinal carcinoma. Distant metastases occur in half of patients and are responsible for most cancer-related deaths. Tumor hypoxia is central to the pathogenesis of metastases. Myo-Inositoltrispyrophosphate (ITPP), a nontoxic, antihypoxic compound, has recently shown significant benefits in experimental cancer, particularly when combined with standard chemotherapy. Whether ITPP protects from distant metastases in primary colon cancer is unknown. Methods: ITPP alone or combined with FOLFOX was tested in a mouse model with cecal implantation of green fluorescent protein-labeled syngeneic colorectal cancer cells. Tumor development was monitored through longitudinal magnetic resonance imaging-based morphometric analysis and survival. Established serum markers of tumor spread were measured serially and circulating tumor cells were detected via fluorescence measurements. Results: ITPP significantly reduced the occurrence of metastases as well as other indicators of tumor aggressiveness. Less circulating tumor cells along with reduction in malignant serum markers (osteopontin, Cxcl12) were noted. The ITPP benefits also affected the primary cancer site. Importantly, animals treated with ITPP had a significant survival benefit compared with respective controls, while a combination of FOLFOX with ITPP conferred the maximum benefits, including dramatic improvements in survival (mean 86 vs 188 d). Conclusions: Restoring oxygen in metastatic colon cancer through ITPP inhibits tumor spread and markedly improves animal survival; an effect that is enhanced through the application of subsequent chemotherapy. These promising novel findings call for a clinical trial on ITPP in patients with colorectal cancer, which is under way. Abstract : Supplemental Digital Content is available in the text